Ekonomi Politik Islam Pengelolaan Zakat Profesi PNS oleh Baitul Mal - BURHANUDDIN BURHANUDDIN; FAISAR ANANDA ARFA; SAPARUDDIN SIREGAR (Universitas Sumatera Utara, 2017)
This research is aims to find out how much the influence of Zakah on Civil Servant Profession and Development conducted by Baitul Mal on Economic Empowerment Society in East Aceh. The research sample is taken from 3 (three) sub-districts, namely Simpang Jernih, Peureulak Barat and Peudawa Sub-districts for 3 (three) months from 7 May to 7 July 2016. The research design used is quantitative research design using linear regression analysis multiple and supported by model test and statistical test using the help of program Eviews 8 and SPSS 16.0. The results showed that the zakah received and variable construction can explain mustahik income of about 33.38%, while 66.62% is explained by other factors. Simultaneously variables that receive alms from the treasury construction affects income mustahik using alpha 5%. Zakah received a positive and significant impact on revenue mustahik. Zakah profession salary civil servants in baitul mal East Aceh in accordance with the purpose and objectives of Islamic economics.